المراجعة المستمرة لحوكمة المؤسسات في ظل التجارة الإلكترونية - صونية, بوزاهر (Recherches économiques et managériales; Vol. 14 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
شهد الربع الأخير من القرن العشرين نمواً هائلاً في متغيرات بيئة الممارسة وكان من أهم هذه التغيرات ما يعرف بتكنولوجيا المعلومات والتجارة الإلكترونية وما ينطويان عليه من متغيرات فرعية، وكان لهذه التغيرات البيئية تأثير ملموس وجوهري على ممارسات الأعمال ومن ثم على نظام المعلومات المحاسبية، وبالضرورة على تشكيلة خدمات مراجع الحسابات، حيث أدى إلى ظهور نظم المعلومات المحاسبية الفورية، وبالتالي فقد لزم الأمر أن يتم تطوير مداخل ممارسة المراجعة الخارجية، فطبيعة معاملات العملاء في الوسط الافتراضي تفرض التحول من المراجعة التقليدية إلى المراجعة المباشرة المستمرة للمعلومات المحاسبية الكترونياً، والتأكد من مدى تطبيقها لمبادئ الحوكمة الدولية لضمان حقوق أصحاب المصالح في هذا الوسط، وقد زاد الاهتمام بها في الآونة الأخيرة بسبب تمكنها من تخفيض تكاليف المراجعة بالمقارنة بالمراجعة التقليدية إلى المستويات التي تحقق تطبيقها بكفاءة وتماشيا والتطورات الحادثة في الوسط والتحول من الأعمال التقليدية إلى الأعمال الإلكترونية. الكلمات المفتاحية : الحوكمة، الحوكمة الفورية، المراجعة المستمرة، التجارة الإلكترونية. Abstract     The last quarter of the twentieth century saw tremendous growth in the practice  environment variable, the most important of these changes is known as information technology and e-commerce, these changes are significant and fundamental impact on business practice then on the accounting information system, and necessarily on a variety of auditor services, which led to the appearance of the immediacy accounting information systems, consequently it’s necessary to develop the practice entrances of external audit. The nature of customer transactions in the hypothetical middle imposes a shift from the traditional audit to the continuous and direct audit of accounting information electronically, and ascertain the extent of application of the principles of international governance to ensure the rights of stakeholders in this medium, the interest of immediate audit has increased recently because of enabling  them to reduce audit costs compared to traditional audit to check the levels that applied efficiently and in keeping with the developments in this medium and the shift from traditional business to e-business Keywords: Governance, immediate governance, continuous audit, e-commerce